The Copyright Challenges of Cultural Heritage Digitization and its Countermeasures - Zheng, Yike (International Journal of Social Sciences and Public Administration, 2024)
There is a conflict between the public and private interest attributes of cultural heritage digitization achievements in practice. In order to balance this conflict, on the one hand, although cultural heritage digitization achievements are the achievements derived from cultural heritage of public nature, due to the fact that they have inevitably intervened in the process of digitization with wisdom and labour, and generated corresponding property value, they have the attribute of private interest, therefore, their private interest should be confirmed by way of copyright compensation, and differentiation should be made in respect of different types of cultural heritage digitization assets, reasonably lower the standard of originality for recognizing cultural heritage digitization achievements as works, stimulate the power of the market, and increase the enthusiasm of subjects engaged in digitization in creation and dissemination. On the other hand, even if there are private interests in the cultural heritage digitization achievements, the protection and inheritance of cultural heritage should still be based on public welfare due to the positioning of the public welfare attribute of cultural heritage. Therefore, for the practice of cultural heritage departments claiming copyright over digitization achievements and restricting the public's free use, it should be regulated through copyright restrictions.